The role of an enzymatically inactive CPAF mutant vaccination in Chlamydia muridarum genital tract infection. (November 2021) - Chen, Hui; Peng, Bo; Yang, Chunfen; Xie, Lijuan; Zhong, Shufang; Sun, Zhenjie; Li, Zhongyu; Wang, Chuan; Liu, Xiao; Tang, Xin; Zhong, Guangming; Lu, Chunxue
Abstract: Chlamydia trachomatis urogenital tract infection causes pelvic inflammatory disease and infertility, increases the risk of co-infection with HPV and HIV. Chlamydial vaccination is considered the most promising approach to prevent and control its infection. Among various chlamydial vaccine candidates, chlamydial protease-like activity factor (CPAF) have been reported to provide robust protective immunity against genital chlamydial infection in mice with reduced vaginal shedding and oviduct pathology. However, CPAF is a serine protease which has enzymatical activity to degrade a large number of substrates. In order to increase the safety of CPAF vaccine, in this study, we used a mutant CPAF that is deficient in enzymatical activity to determine whether proteolytic activity of CPAF affect its vaccine efficacy. The wild type or mutant CPAF immunization causes a significant lower chlamydial shedding from the vaginal and resolve the infection as early as day 20, compared to day 28 in adjuvant control mice. More important, reduced upper reproductive tract pathology were also observed in these two groups. The mutant or wild type CPAF immunization induced not only robust splenic IFN-γ and serum IgG2a but also sIgA secretion in the vaginal fluids. Furthermore, neutralization of chlamydia with immune sera did not provide protection against oviduct pathology. However, adoptive transfer of CD4 + splenocytes isolated from the mutant or wild type CPAF immunized mice resulted in a significant and comparable reduced oviduct pathology. Our results indicate mutant CPAF vaccination is as same efficacy as wild type, and the protection relies on CD4 + T cells, which will further promote the development of CPAF as clinical chlamydial vaccine. Highlights: ● Recombinant CPAF catalytic mutant (Mut) loses its enzymatic activity ● CPAF (Mut) induced comparable enhancement of genital chlamydial clearance and reduction of upper genital pathologies when compared to CPAF (Wt) ● The CPAF (Mut) still maintains both conformational and linear epitopes to induce high CPAF specific antibody and IFN-γ production ● It is CD4 + T lymphocyte but not neutralization antibody plays important role in protection against C. muridarum infection